Diabetic cardiomyopathy—an under-recognized cause of heart failure in diabetic patients: Diabetična kardiomiopatija – pogosto neprepoznan vzrok srčnega popuščanja pri bolnikih s sladkorno boleznijo - Šarun, David; Kanič, Vojko; Sinkovič, Andreja (Acta Medico-Biotechnica, 2021)
Cardiovascular disorders are the major cause of morbidity and mortality in patients with diabetes mellitus. The prevalence of heart failure is 3–5 times higher in diabetic patients compared with the general population. Diabetic cardiomyopathy is defined as a diabetes-specific disorder characterized by the presence of functional or morphologic changes in the diabetic myocardium, unrelated to coronary artery disease, valvular dysfunction, and arterial hypertension. Hyperglycemia, insulin resistance, and hyperinsulinemia are the major abnormalities affecting cardiac metabolism, mitochondrial function, and cellular growth. Cardiac changes are more pronounced in type 2 diabetes mellitus compared with type 1 diabetes mellitus. The restrictive phenotype is a common presentation with left ventricular remodeling and diastolic dysfunction, while the left ventricular ejection fraction is preserved. The dilated phenotype with eccentric remodeling and reduced left ventricular ejection fraction is uncommon and might be a hallmark of advanced disease. Although no specific treatment has been recommended, new-generation anti-diabetic drugs (sodium-glucose co-transporter-2 inhibitors) have yielded promising results and extensive research is underway.
Keywords: diabetes mellitus; heart failure; diabetic cardiomyopathy; left ventricular diastolic dysfunction